The Role of PPARγ in Advanced Glycation End Products-Induced Inflammatory Response in Human Chondrocytes - Ma, Chi; Zhang, Ying; Li, Yu-qing; Chen, Cheng; Cai, Wei; Zeng, Yue-lin (PloS one, 2015)
Advances made in the past ten years highlight the notion that peroxisome proliferator-activated receptors gamma (PPARγ) has protective properties in the pathophysiology of osteoarthritis (OA). The aim of this study was to define the roles of PPARγ in AGEs-induced inflammatory response in human chondrocytes. Primary human chondrocytes were stimulated with AGEs in the presence or absence of neutralizing antibody against RAGE (anti-RAGE), MAPK specific inhibitors and PPARγ agonist pioglitazone. The expression of IL-1, MMP-13, TNF-α, PPARγ, nuclear NF-κB p65 and cytosol IκBα was determined by western blotting and real-time PCR. AGEs could enhance the expression of IL-1, TNF-α, and MMP-13, but the level of PPARγ was decreased in a time- and dose-dependent manner, which was inhibited by anti-RAGE, SB203580 (P38 MAPK specific inhibitor) and SP600125 (a selective inhibitor of JNK). PPARγ agonist pioglitazone could inhibit the effects of AGEs-induced inflammatory response and PPARγ down-regulation. In human chondrocytes, AGEs could induce cytosol IκBα degradation and increase the level of nuclear NF-κB p65, which was inhibited by PPARγ agonist pioglitazone. In primary human chondrocytes, AGEs could down-regulate PPARγ expression and increase the inflammatory mediators, which could be reversed by PPARγ agonist pioglitazone. Activation of RAGE by AGEs triggers a cascade of downstream signaling, including MAPK JNK/ p38, PPARγ and NF-κB. Taken together, PPARγ could be a potential target for pharmacologic intervention in the treatment of OA.